FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN KONDOM PADA KLIEN WANITA PEKERJA SEKS (WPS) DALAM UPAYA PENCEGAHAN INFEKSI MENULAR SEKSUAL (IMS) DI KELURAHAN BANDUNGAN - Yuni Sri Utama; Kusyogo Cahyo; Ratih Indraswari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
WHO estimates that there are 350 million Sexual Transmitted Infections (STIs) cases in developing countries. The reason is due to the low usage of condom in high-risk sexual conducts. Integrated Biological and Behavioral Surveillance on 2011 reported condom usage in men at high-risk of being infected is still at 8%, considered low. The aim of this research is to analyze the pertinent factors to sex worker’s behavior of using condom in order to prevent STIs in Bandungan region. This research used quantitative method with cross-sectional approach. The amount of samples were 100 respondents gathered with accidental sampling. In analyzing data, univariate and bivariate analysis were used with Chi-square as its statistic test. The study showed that majority of the respondents were below 45 years old (72%), had a higher education (56%), had an informal job (90%), married (64%), had a high income (≥ Rp. 1.419.000,00) (87%), had a lack knowledge regarding condom usage (54%), had a lack condom usage support (51%), had an adequate number of condoms (59%), had a condom availability (61%), didn’t get enough support from woman sex worker (58%), didn’t get enough support from their pimps (56%). Bivariate analysis showed there were correlations between education level (p=0,009), income (p=0,017), knowledge (p= 0,001), attitude (p=0.001), condom availability (p=0.015), and woman sex worker support in client’s condom usage (p=0,001) with woman sex worker client’s behavior of using condom in order to prevent STIs infection. Meanwhile there were no correlations between age (p = 0.504), marital status (p = 0.835), occupation (p = 0.317), affordability of condoms (p = 0.412), and the support from pimps (PTL) (p = 0.840) with woman sex worker client’s behavior of using condom in order to prevent STIs infection.